Contribution of Agricultural Productivity to Industrialization in Africa: Does Infrastructural Development Matter? - Anchi, Evina Ofeh; Aboubakary, Ndzembanteh; Edoh, Ofeh Marilyn (Finance & Economics Review, 2023)
Purpose: The objective of this study is to investigate the direct and indirect effects of agricultural productivity on industrialization. It also looks for the mediating role of infrastructural development on the effects of agricultural productivity on industrialization. Method: The system Generalized Method of Moments (GMM) methodology for 45 African countries is applied. It covers the period from 2005 to 2022. Results: The results show that agricultural productivity has a positive significant role on industrialization in Africa. This result is robust when industrialization is measured by employment in industry (EMIND). Infrastructural development has an enhancing role on the agricultural productivity-industrialization nexus. These results are robust for the two different measures of industrialization but are more enhancing on Employment in Industry than on Manufacturing Value Added (MVA). The study also observes that agricultural productivity interacts with the Water and Sanitation Index (WSS) on MVA to yield a positive net effect. Moreover, agricultural productivity interacts with ICT (Information and Communication Technology) and ECI (Electricity composite index) on both MVA and EMIND to yield positive synergy effects. Implications: The Electricity Composite Index is still not sufficient in Africa. Equally, there is a need for some countries like Chad, Ethiopia, Mozambique, and Niger to boost WSS above this threshold of 32.96 since this threshold is below the mean value for Africa as a whole. Policy-wise, it could be recommended that both agricultural productivity and infrastructural development should be strengthened, with emphasis on electricity, so as to achieve the much-needed level of industrialization for Africa.